Implementation of Environmental Management Accounting Practices on the Financial Performance of Wooden Furniture Manufacturing in South Africa - Pillay, Malani; Msomi, Thabiso Sthembiso; Aliamutu, Kansilembo (International Journal of Economics and Financial Issues, 2025)
The research investigates the relationship between Environmental Management Accounting (EMA) practices and improving the financial performance of wooden furniture manufacturing. It responds to the increasing interest in sustainable practices within manufacturing industries and their impact on financial performance, making it relevant to those interested in sustainable business strategies and environmental accounting. The study aims to bridge the gap in understanding how EMA practices affect the financial performance of wooden furniture manufacturers. The central premise is that integrating EMA can enhance financial performance by reducing costs, improving resource efficiency, and boosting the company’s reputation, thus contributing to long-term financial sustainability. We used both Ordinary Least Squares (OLS) and a two-step system generalization method of moments estimator in our analysis. Data was collected from 20 listed companies, resulting in 80 observations. Variables for EMA included the Environmental Investment Ratio (EIR), Environmental Expenses Ratio (EER), Natural Capital Cost (NCC), and Emissions Intensity (EMI). The data, covering the period from 2020 to 2023, was sourced from financial reports, sustainability reports, and industry publications of wooden furniture manufacturing companies. The study employs quantitative analysis techniques to assess the relationship between EMA practices and financial performance indicators such as profitability, cost savings, and resource efficiency. The results show a positive correlation between EMA implementation and financial performance. Companies adopting EMA practices reported improved profitability, significant cost reductions in waste management and resource usage, and overall enhanced financial performance compared to those not implementing these practices. This research adds to the body of knowledge by providing empirical evidence on the benefits of EMA in the manufacturing sector. It suggests that wooden furniture manufacturers can achieve financial sustainability by adopting EMA practices, which improve environmental performance and lead to better financial performance. The study also emphasizes the need for policymakers to promote the adoption of sustainable practices in the industry.